A systematic review of multidomain and lifestyle interventions to support the intrinsic capacity of the older population - Bevilacqua, Roberta; Soraci, Luca; Stara, Vera; Riccardi, Giovanni Renato; Corsonello, Andrea; Pelliccioni, Giuseppe; Lattanzio, Fabrizia; Casaccia, Sara; Möller, Johanna; Wieching, Rainer; Ogawa, Toshimi; Watanabe, Suichiro; et al. (Frontiers in Medicine, 2022)
Introduction: The focus on intrinsic capacity (IC) could help clinicians to design interventions to improve the health of the older population. This review aims to map the current state of the art in the field of multi-domain interventions based on the IC framework, to allow health professionals in identifying personalized clinical interventions, oriented to empower the older people with a holistic and positive approach. Methods: A systematic review of the literature was conducted in July 2021 analyzing manuscripts and articles of the last 10.5 years from PubMed, Scopus, Embase, Google Scholar and Elsevier databases. A total of 12 papers were included. Results: The majority of successful interventions are based on a goal setting approach where the older people are involved in the definition of the strategy to follow to remain active and independent. None of the study have used the IC as a framework to design a clinical intervention. Conclusion: To the best of our knowledge, no other reviews are reported in the literature regarding the IC. Our study offers several research directions, which may take the existing debates to the next level.